2005
DOI: 10.1002/art.20924
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity, physical fitness, and general health perception among individuals with rheumatoid arthritis

Abstract: Objective. To describe self-reported physical activity and physical fitness and to identify correlates of physical activity and general health perception. Methods. Data on self-reported physical activity, physical fitness, activity performance, and disease activity were collected from a sample of 298 patients with rheumatoid arthritis (RA). Results. Forty-seven percent of our sample reported physical activity behaviors that did not comply with public health recommendations. A majority of the patients had decre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
121
0
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(140 citation statements)
references
References 33 publications
(37 reference statements)
15
121
0
2
Order By: Relevance
“…Established HEPA at baseline predicted being in the stable high trajectory versus the 2 other groups, and self-efficacy for exercise predicted being in the stable high versus the stable low group. These findings were expected and are in line with the few existing studies on correlates of physical activity in RA, indicating positive associations between current and previous physical activity (39), as well as arthritisspecific self-efficacy for daily activities (40).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Established HEPA at baseline predicted being in the stable high trajectory versus the 2 other groups, and self-efficacy for exercise predicted being in the stable high versus the stable low group. These findings were expected and are in line with the few existing studies on correlates of physical activity in RA, indicating positive associations between current and previous physical activity (39), as well as arthritisspecific self-efficacy for daily activities (40).…”
Section: Discussionsupporting
confidence: 89%
“…Considering the inconsistency of previous research (13,(41)(42)(43), our research question regarding sex and physical activity over 2 years was more explorative. One reason for the disparate findings in previous studies may be the different study designs and methods of measurement.…”
Section: Discussionmentioning
confidence: 99%
“…This relatively low rate is comparable with the proportion of approximately 1% that can be extrapolated from the implementation studies of the Arthritis Foundation Aquatic Program (AFAP) and the Patients with Arthritis Can Exercise (PACE) program, developed by the Arthritis Foundation in the US (5). There are a number of possible explanations for the low number of participants that were already identified in previous studies (22,23). An attendance frequency of 2 times per week is time consuming.…”
Section: Discussionsupporting
confidence: 55%
“…RF was present in 61% of the women and 58% of the men at the time of inclusion. Of the 59 patients who dropped out and did not complete the EDAQ, 37 were women (median age 50 years, IQR 27 at inclusion) and 22 were men (median age 59 years, IQR 23 at inclusion). Age, erythrocyte sedimentation rate (ESR), plasma C-reactive protein (CRP), DAS28 (28), grip force (21), and HAQ score (29) did not differ between the study group and the dropouts, whereas the dropouts reported significantly more general pain on a 0 -100-mm visual analog scale (VAS) (P ϭ 0.023) and more tender joints (P ϭ 0.04).…”
Section: Introductionmentioning
confidence: 99%